1992
DOI: 10.1021/bi00130a003
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the lipid-exposed regions in the Torpedo californica nicotinic acetylcholine receptor

Abstract: To identify regions of the Torpedo nicotinic acetylcholine receptor (AchR) interacting with membrane lipid, we have used 1-azidopyrene (1-AP) as a fluorescent, photoactivatable hydrophobic probe. For AchR-rich membranes equilibrated with 1-AP, irradiation at 365 nm resulted in covalent incorporation in all four AchR subunits with each of the subunits incorporating approximately equal amounts of label. To identify the regions of the AchR subunits that incorporated 1-AP, subunits were digested with Staphylococcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
140
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(152 citation statements)
references
References 57 publications
(63 reference statements)
11
140
1
Order By: Relevance
“…Table 1 lists mass accuracies of the detected photolabeled peptides. Some photolabeled peptides deviated markedly from (46,47,55). C427 and T431 (shown in bold underlined type with red͞green circles) were identified by TID incorporation both in previous studies and in the present study.…”
Section: Ms For Analyzing Ion Channel Conformationalsupporting
confidence: 75%
See 1 more Smart Citation
“…Table 1 lists mass accuracies of the detected photolabeled peptides. Some photolabeled peptides deviated markedly from (46,47,55). C427 and T431 (shown in bold underlined type with red͞green circles) were identified by TID incorporation both in previous studies and in the present study.…”
Section: Ms For Analyzing Ion Channel Conformationalsupporting
confidence: 75%
“…4 illustrate that M4 photolabeled residues identified by this study reside on the same helical face as residues identified in previously published reports. Thus the present results further define the lipid-exposed face of the M4 transmembrane ␣-helix (46,47).…”
Section: Photolabeled Residues Identified Within the M3-m4supporting
confidence: 72%
“…No internal cleavages were detected within this region (although this region is primarily hydrophobic and offers few potential targets for proteolysis). Given the reported pattern of lipophilic photoactivable reagent incorporation within the M4 region of nAchR (32), the presence of a phosphorylation site at Ser-391, and the extracellular location of the C terminus, it is expected that a single TM ␣-helix is located within residues 392-416.…”
Section: Resultsmentioning
confidence: 99%
“…The M2 and M1 segments from each subunit associate around a central axis to form part of the aqueous ion channel. In contrast, the M4 and M3 segments have been shown to have the largest contact with lipid (Blanton & Cohen, 1992.…”
Section: Introductionmentioning
confidence: 92%